How do green knowledge management and green technology innovation impact corporate environmental performance? Understanding the role of green knowledge acquisition - Sahoo, Saumyaranjan; Kumar, Anil; Upadhyay, Arvind (Business strategy and the environment, 2023)
Increasing regulatory obligations to adapt and execute environmentally friendly operations make it critical for businesses to pursue strategies that can strengthen their competitive edge in the market. Academics and practitioners alike have recently gravitated toward exploring how knowledge acquisition activities might improve business outcomes. To address this growing research interest, this study investigates the critical roles of green knowledge acquisition in enhancing green knowledge management and green technology innovation activities in improving corporate environmental performance, positioning resource commitment as a moderator. The research model has been assessed using structural equation modeling with survey data from 283 Indian manufacturers, demonstrating that green knowledge acquisition significantly impacts green knowledge management and green technology innovation. The statistical findings also show that green technology innovation acts catalyzes the translation of green knowledge management into improved corporate environmental performance. The results demonstrate that resource commitment moderates green knowledge acquisition's interaction with green knowledge management and green technology innovation, providing practical insights enabling managers to focus on planning, allocating, and budgeting resources for effective green practices that can contribute to improving corporate environmental performance.